THE FUTURE OF ASIAN VALUES: WILL THEY BE STRENGTHENED OR REPLACED BY INDIVIDUALISM? - Samariddin, Elmirzaev; Azamat, Botirov; Javlon, Kurbonov; Navruz, Shavkatov; Hamidulla, Khalikov (International Journal of Psychosocial Rehabilitation, 2020)
About two decades ago, East Asia was hot, as were "Asian values". In explaining East Asia's extraordinary economic development - what the World Bank called a "miracle" - many believed that culture played a key role. This paper studies the literature about Asian values and the impact of Asian values on Asian Financial Crisis. According to results, development can be achieved without losing cultural values.